2013
DOI: 10.1002/jhet.1513
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of Novel Thiazole Substituted Pyrazole Derivatives

Abstract: 10a-g) have been synthesized by using Vilsmeier Haack formylation and Hantzsch reaction in high yield.All the synthesized compounds were tested qualitative (Zone of inhibition) and quantitative antimicrobial activities (MIC). Most of the synthesized compounds showed potent antimicrobial activity against gram positive and gram negative bacteria as well as fungi species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…Thus, there is a real need for new therapeutic options for the treatment of cryptococcosis. With this goal, and based on the wide range of biological activities exhibited by thiazole heterocycles [16,17,18], we report here the synthesis and screening of thiazole heterocyclic compounds (Figure 1 and 2) with therapeutic potential against cryptococcosis. Some of these molecules have shown promising antifungal activity in vitro.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Thus, there is a real need for new therapeutic options for the treatment of cryptococcosis. With this goal, and based on the wide range of biological activities exhibited by thiazole heterocycles [16,17,18], we report here the synthesis and screening of thiazole heterocyclic compounds (Figure 1 and 2) with therapeutic potential against cryptococcosis. Some of these molecules have shown promising antifungal activity in vitro.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Thiosemicarbazones and their thiazole heterocyclic derivatives are of great importance in pharmacology due to their broad range of biological activities, such as anticonvulsant, antimicrobial, and antiparasitic activities (Gaikwad, Patil, Bobade, 2013;Souza et al, 2013;Bharti et al, 2010;Siddiqui et al, 2009;Oliveira et al, 2008a;Souza, 2005;Dimmock et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The thiazole compounds, which possess sulfur and nitrogen, are widely distributed in natural products and have promising biological activity, representing a class of substances that attracts great synthetic interest (21). Some studies have reported the synthesis of new thiazoles with anti-inflammatory, antibacterial, anticancer, and anti-HIV activities (22)(23)(24)(25).…”
mentioning
confidence: 99%